Molecular Distinction between Specification and Differentiation in the Myogenic Basic Helix-Loop-Helix Transcription Factor Family - Bergstrom, Donald A. (American Society for Microbiology, 2001)
The myogenic basic helix-loop-helix (bHLH) proteins regulate both skeletal muscle specification and differentiation: MyoD and Myf5 establish the muscle lineage, whereas myogenin mediates differentiation. Previously, we demonstrated that MyoD was more efficient than myogenin at initiating the expression of skeletal muscle genes, and in this study we present the molecular basis for this difference. A conserved amphipathic alpha-helix in the carboxy terminus of the myogenic bHLH proteins has distinct activities in MyoD and myogenin: the MyoD helix facilitates the initiation of endogenous gene expression, whereas the myogenin helix functions as a general transcriptional activation domain. Thus, the alternate use of a similar motif for gene initiation and activation provides a molecular basis for the distinction between specification and differentiation within the myogenic bHLH gene family.